Importancia del periodismo comunitario en la difusión de la cultura de la Parroquia Guasaganda del cantón La Maná, año 2022 - Pastuña Chugchilan, Marianela Elizabeth (2022)
Community journalism is the most heartfelt expression of a community, and in practice it means that every local resident has the opportunity to provide information that contributes to community organizations. However, in support of the development of projects of national transformation and construction of the masses, this activity is currently not understood by the media, not even by the journalists who are responsible for prominence and participatory democracy and the right to freedom. information and the strength of communication. When reviewing the bibliography, the historical evolution of the development of journalism can be identified, attesting to some of the characteristics it presents, such as: Journalistic communication as a permanent process, universe of community journalism, cultural dysfunction, and in some cases, they show Issues and Assumed in the form of a complaint, this means a lack of format when it comes to community journalism. On the other hand, the Organic Law of Communication in article 70 expresses the typology of the media in which it establishes three, the public, private, and community media. The research design was carried out with the descriptive method, survey techniques and direct observation with its instrument, the questionnaire and observation sheet.